2017
DOI: 10.15252/embr.201743922
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 deficiency impairs chemotaxis and microglial responses to neuronal injury

Abstract: Sequence variations in the triggering receptor expressed on myeloid cells 2 (TREM2) have been linked to an increased risk for neurodegenerative disorders such as Alzheimer's disease and frontotemporal lobar degeneration. In the brain, TREM2 is predominantly expressed in microglia. Several disease-associated TREM2 variants result in a loss of function by reducing microglial phagocytosis, impairing lipid sensing, preventing binding of lipoproteins and affecting shielding of amyloid plaques. We here investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
217
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 258 publications
(259 citation statements)
references
References 69 publications
23
217
4
Order By: Relevance
“…MGnD microglia may also be protective and represent an initial response to neuronal injury. As we showed recently, TREM2 deficiency may lock microglia in a homeostatic state (Mazaheri et al, 2017) and block essential defense functions of microglia during disease progression. In summary, we demonstrate that the TREM2-APOE pathway induces a microglia phenotype switch from a homeostatic to neurodegenerative phenotype.…”
Section: Discussionmentioning
confidence: 76%
“…MGnD microglia may also be protective and represent an initial response to neuronal injury. As we showed recently, TREM2 deficiency may lock microglia in a homeostatic state (Mazaheri et al, 2017) and block essential defense functions of microglia during disease progression. In summary, we demonstrate that the TREM2-APOE pathway induces a microglia phenotype switch from a homeostatic to neurodegenerative phenotype.…”
Section: Discussionmentioning
confidence: 76%
“…These observations suggest that ABI3 expressed on microglia in NC, AD, and NHD brains might positively regulate their motility and migration capacity via formation of podosomes, particularly when the activity of c-ABL tyrosine kinase is suppressed. In contrast, ABI3 mRNA expression is upregulated in TREM2-deficient microglia that exhibit a reduction in chemotaxis and migration (25).…”
Section: Discussionmentioning
confidence: 95%
“…It is known that myelinassociated lipids can trigger TREM2 signaling in vitro (Poliani et al, 2015;Wang et al, 2015) and Trem2 knockout mice are not capable of responding properly to myelin damage upon cuprizone-induction demyelination (Cantoni et al, 2015;Poliani et al, 2015). This is in line with a reduced sensing of myelinassociated lipids (Poliani et al, 2015;Wang et al, 2015) as well as a general defect of chemotaxis of Trem2-deficient microglia (Mazaheri et al, 2017). Our findings support the idea that microglial nodulelike structures are also formed during physiological aging and may represent a clearance mechanism of minor white matter insults.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, loss of Trem2 or its signaling adaptor DNAX activation protein of 12 kDa (DAP12) has been shown to affect proliferation and survival of macrophages (Otero et al, 2012;Wu et al, 2015) and microglia in a CSF1 and sTrem2 concentration-dependent manner. Moreover, transcriptomic analyses revealed that microglia may be locked in a homeostatic stage in the absence of Trem2 (Mazaheri et al, 2017). Moreover, transcriptomic analyses revealed that microglia may be locked in a homeostatic stage in the absence of Trem2 (Mazaheri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%